Model Pembelajaran Bahtsul Masail untuk Membangun Moderasi Beragama - Ulum, Mokhamad Miptakhul (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2021)
Bahtsul masail is an academic forum organized by several Islamic boarding schools in Indonesia, including the Asma' Chusna Islamic Boarding School Kranji Kedungwuni Pekalongan. This forum is held both within the pesantren's internal and between pesantren and among the Islamic organization Nahdlatul Ulama. Islamic boarding schools are rigid educational institutions, but the bahtsul masail at the Asma' Chusna Kranji Islamic Boarding School Kedungwuni Pekalongan is proof of the openness and moderation pesantren education. This study aims to elaborate the practice of bahtsul to build moderate attitudes and behavior of the students. This qualitative-reflective research proves that the practice of bahtsul masail can train students to think critically, dynamically, and democratically in responding to socio-religious problems and challenges. This practice also enhances the emotional and friendly relationship between the participants. However, this practice has a drawback, namely when the results of the bahtsul masail are not distributed and socialized to the public.